Mitochondrial quality control in hepatic ischemia-reperfusion injury - LiuSong Wang; Zan Jie Feng; Xuan Ma; Kai Li; Xin Yao Li; Yi Tang; Cijun Peng (Heliyon, 2023)
Hepatic ischemia-reperfusion injury is a phenomenon in which exacerbating damage of liver cells due to restoration of blood flow following ischemia during liver surgery, especially those involving liver transplantation. Mitochondria, the energy-producing organelles, are crucial for cell survival and apoptosis and have evolved a range of quality control mechanisms to maintain homeostasis in the mitochondrial network in response to various stress conditions. Hepatic ischemia-reperfusion leads to disruption of mitochondrial quality control mechanisms, as evidenced by reduced mitochondrial autophagy, excessive division, reduced fusion, and inhibition of biogenesis. This leads to dysfunction of the mitochondrial network. The accumulation of damaged mitochondria ultimately results in apoptosis of hepatocytes due to the release of apoptotic proteins like cytochrome C. This worsens hepatic ischemia-reperfusion injury. Currently, hepatic ischemia-reperfusion injury protection is being studied using different approaches such as drug pretreatment, stem cells and exosomes, genetic interventions, and mechanical reperfusion, all aimed at targeting mitochondrial quality control mechanisms. This paper aims to provide direction for future research on combating HIRI by reviewing the latest studies that focus on targeting mitochondrial quality control mechanisms.